2019
DOI: 10.1002/kjm2.12087
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Numb/Notch signaling pathway increases radiation sensitivity in human nasopharyngeal carcinoma cells

Abstract: Radiation therapy is the primary treatment for primary nasopharyngeal carcinoma (NPC). The aim of this study is to identify the effect of the Numb/Notch signaling pathway on radiation sensitivity in human NPC cells. NPC tissues and normal nasopharyngeal tissues were collected. To evaluate the regulatory effects of the Numb/Notch signaling pathway, NPC cells were subjected to radiotherapy and various doses of the Numb/Notch signaling pathway inhibitor gamma secretase inhibitor (GSI). Next, the expression of Not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…NUMB expression levels were also decreased in tongue cancer and its overexpression inhibited cell proliferation, migration and invasion via regulating Notch1 signaling (16). In nasopharyngeal carcinoma, the Notch signaling pathway was regulated by NUMB, which promoted cancer cell survival, migration and invasion, in addition to inhibiting colony formation and apoptosis (17). Moreover, NUMB expression has been reported to be regulated by miR-146a in oral carcinoma (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NUMB expression levels were also decreased in tongue cancer and its overexpression inhibited cell proliferation, migration and invasion via regulating Notch1 signaling (16). In nasopharyngeal carcinoma, the Notch signaling pathway was regulated by NUMB, which promoted cancer cell survival, migration and invasion, in addition to inhibiting colony formation and apoptosis (17). Moreover, NUMB expression has been reported to be regulated by miR-146a in oral carcinoma (18).…”
Section: Discussionmentioning
confidence: 99%
“…NUMB is an endocytic adaptor protein that is localized in the basement layer of polarized epithelial cells (14). In previous studies, NUMB has been found to serve crucial roles in human cancer (15)(16)(17)(18); for example, NUMB expression levels were decreased in ovarian cancer, which regulated cancer cell proliferation, invasion and epithelial-mesenchymal transition through regulating the p21 (RAC1) activated kinase 1/β-catenin signaling pathway (15). NUMB expression levels were also decreased in tongue cancer and its overexpression inhibited cell proliferation, migration and invasion via regulating Notch1 signaling (16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inhibition of the Numb/Notch signaling pathway increases radiation sensitivity in human nasopharyngeal carcinoma cells. 361 In this part, we primarily discuss the regulation of oxidative stress by EBV, the role of EBV lytic reactivation in EBVassociated diseases and the following radiation therapy. A better understanding of the relationship between them may lead to develop novel prevention and therapeutic strategies for EBVassociated diseases and facilitate the development of novel strategies against radiation-resistant tumors.…”
Section: Biomarkers Of Chemotherapy For Ebv-associated Tumorsmentioning
confidence: 99%
“…NPC is considered a rare cancer in most parts of the world, but it has high morbidity and mortality rates due to its early metastasis and chemotherapy toxicity 21 , 22 . Radiation therapy is the main treatment for NPC, but radiation resistance can prevent effective treatment 23 . KDM4A has been found to contribute to the Warburg effect in the NPC process 8 , but the specific mechanism of KDM4A in NPC remains poorly defined.…”
Section: Discussionmentioning
confidence: 99%